2014
DOI: 10.1111/pala.12116
|View full text |Cite
|
Sign up to set email alerts
|

Origin and early diversification of the phylum Cnidaria Verrill: major developments in the analysis of the taxon's Proterozoic–Cambrian history

Abstract: Diploblastic eumetazoans of the phylum Cnidaria originated during the Neoproterozoic Era, possibly during the Cryogenian Period. The oldest known fossil cnidarians occur in strata of Ediacaran age and consist of polypoid forms that were either nonbiomineralizing or weakly so. The oldest possible anthozoans, including the genus Ramitubus, may be related to tabulate corals and occur in the Doushantuo Lagerstätte (upper Doushantuo Formation, South China), the age of which is poorly constrained (approximately 585 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 73 publications
0
93
0
6
Order By: Relevance
“…They suggested that Medusozoa (Scyphozoa + Hydrozoa) formed a sister group to Octocorallia, and that these together were a sister group to Hexacorallia (Kayal et al, 2013). The phylogeny was cited as potentially supporting the 'polyp before medusa' hypothesis of cnidarian evolution (Ax, 2012), a theme taken up by Dzik et al (2017) in the context of the fossil record of the tubular cnidarian Sphenothallus Hall, 1847 and related Lower Paleozoic taxa (Tynan, 1983;Van Iten et al, 2014). Zapata et al (2015) restated the monophyly of Anthozoa, Octocorallia, and Hexacorallia.…”
Section: Systematic Position Of Cambroctoconusmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that Medusozoa (Scyphozoa + Hydrozoa) formed a sister group to Octocorallia, and that these together were a sister group to Hexacorallia (Kayal et al, 2013). The phylogeny was cited as potentially supporting the 'polyp before medusa' hypothesis of cnidarian evolution (Ax, 2012), a theme taken up by Dzik et al (2017) in the context of the fossil record of the tubular cnidarian Sphenothallus Hall, 1847 and related Lower Paleozoic taxa (Tynan, 1983;Van Iten et al, 2014). Zapata et al (2015) restated the monophyly of Anthozoa, Octocorallia, and Hexacorallia.…”
Section: Systematic Position Of Cambroctoconusmentioning
confidence: 99%
“…Cnidarians have a geological record extending back to the Ediacaran (Van Iten et al, 2014, 2016aLiu et al, 2014;Grazhdankin, 2016;Han et al, 2016;Dzik et al, 2017), but the heavily calcified groups of tabulate and rugosan corals that dominate the Paleozoic fossil record first appear in the Ordovician (Scrutton, 1997(Scrutton, , 1999. There are, however, many mineralized Cambrian fossils, particularly in the early Cambrian, that have been considered as possible anthozoans, but their relationships to the major zoantharian and octocorallian groups are uncertain (Zhuravlev et al, 1993;Scrutton, 1997Scrutton, , 1999Debrenne and Reitner, 2001;Han et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fossil muscular impressions of Cambrian cnidarians, such as those of scyphomedusae, have an organization strikingly clear and similar to extant animals [14,15]. The impressions of H. quadriformis are considerably more complicated, probably because of its plane of preservation and possible superposition of morphological structures, making it difficult to reliably reconstruct muscular organization.…”
mentioning
confidence: 99%
“…4a-b) also occurs in the Tamengo Formation, and has been interpreted as a cnidarian, possibly related to the Scyphozoa Walde et al, 1982;Babcock et al, 2005). Van Iten et al (2014) interpreted this fossil as a colunariid scyphozoan, related to other non-erect Ediacaran fossils such as the vendozoan genera Phyllozoon (Jenkins and Gehling, 1978) or Dickinsonia (Sprigg, 1947). Since, in 2012, three-dimensional specimens of Corumbella werneri were found together with two-dimensionally preserved material in a quarry on the western edge of Corumba, it is evident that this species does not belong to the conulariids, but to cloudinids (personal comm.…”
Section: The Precambrian Fossil Record Of the Corumbà Regionmentioning
confidence: 95%